Differentiation of paediatric burn injury by household energy source in South Africa - Rajen Govender; David Kimemia; Nancy Hornsby; Ashley van Niekerk (Journal of Energy in Southern Africa, 2020)
Burn injuries remain a significant cause of death and disability in the global south, with children amongst the most vulnerable. In South Africa, burns are a critical health and economic burden in densely populated and energy-impoverished communities. This study used secondary data on burn injuries from 19 health facilities to differentiate between risk for scalds and flame burns across three household energy sources (firewood, paraffin and electricity). The sample was 2 933 cases of child burn victims, with key analytical procedures being descriptive statistics and logistic regression analysis. Results showed that 52% of burn injury admissions reported electricity as the household energy source used at the time of injury. Most burn injuries were scalds (85.3%), with infants and toddlers at greatest risk. The differentiation between wood and paraffin was associated with a threefold increase in scalds relative to flame burns, while that between paraffin and electricity indicated a sevenfold increase in scalds and nineteen times such an increase between wood and electricity. This was an indication of continued challenges for the country in addressing paediatric burns despite, and in the context of, the continued electrification of poor households. The study recommends improved regulation of electrical appliances used by low-income households, and targeted household safety education initiatives.